Population Pressures, System-Level Inertia and Healthy Aging Policy Revisited - Andrew V. Wister (HealthcarePapers, 2011)
Chappell and Hollander provide support for a set of policy directives formulated for an aging population. An integrated continuum of care model is the fulcrum of the policy prescription, given evidence-based support for its cost-effectiveness; improved quality of care and quality of life; and the success of similar models found in Denmark, Japan and other countries. This commentary addresses the underlying assumptions of these policy recommendations, identifies the major barriers to their implementation and suggests solutions. Improving our understanding of the dynamics of population aging as it relates to health and healthcare use is a necessary requirement to reaching the aims set out by the authors.
Keywords: Aging, public policy, sustainable healthcare system, elderly, healthcare reform, geriatrics